An instance of ovarian calcification in the seabass, Lates calcarifer (Bloch) - Lal, Kuldeep K; Pandey, Ajay K (Indian Journal of Fisheries, 2011)
While studying the seasonal changes in the gonads of the female Lates calcarifer collected from Tambarparani estuary, Korampallan creek along the Tuticorin coast (Gulf of Mannar), out of 311 fish samples examined, one specimen weighing 8.50 kg and total length 925 mm, exhibited partial ovarian calcification. Histological examination of the calcified portion of ovary (after partial decalcification) revealed thickening of the ovigerous lamellae and deposition of calcium in their lumina which were devoid of oocytes whereas the non-clacified part of ovary possessed ova at chromatin nucleus and perinucleolar stage.